An Efficient Multicast Routing Protocol With Quality Of Service For Mobile Ad-Hoc Networks. - Qabajeh, M.; Abdul Hashim, A.H.; Khalifa, O.; Qabajeh, L. (2009)
Mobile ad-hoc network (MANETs) are networks consist of a group of mobile nodes autonomously establishing connectivity via multi-hop wireless communication without any pre-infrastructure or central administration. Multicasting communication serves as one critical operation to support many applications of Ad-hoc networks that achieve group communication rather than pairs of individuals. Multicast routing protocols becomes increasingly important in mobile Ad hoc networks because they effectively coordinate a set of nodes. Also, it provides efficient routing for multimedia applications such as video conferences, military, rescue operations and multi-party games. Such applications are highly demand for Quality of Service (QoS), which makes an efficient QoS multicast routing protocols is very important. The limitations of wireless networks make it necessary to develop a QoS multicast routing protocol that supports multiple QoS constrains with rational overhead. Recently, the availability of inexpensive, less power and small GPS receivers realizes the positionbased multicast routing and improves routes stability. In this work we proposed a model that searches for QoS paths from a single source to a set of destinations. The physical area is partitioned into equal size hexagonal cells and a leader and backup leader nodes is elected to maintain up-to-date information about the network topology. The election process considers several metrics including node mobility, energy and memory. The multicast groups are separated into segments based on their geographical positions and each multicast group has a coordinator. The proposed model is expected to be scalable for large area networks with large number of multicast members. Also, it is expected to achieve a significant reduction in packet and processing overhead.